Determinants of firm performance: The relative importance of economic and organizational factors - Hansen, Gary S.; Wernerfelt, Birger (Strategic Management Journal, 1989)
Abstract We decompose the inter‐firm variance in profit rates into economic and organizational components. Using a representative model from each paradigm we find that both sets of factors are significant determinants of firm performance. Further findings are that the two effects are roughly independent and that organizational factors explain about twice as much variance in profit rates as economic factors.